Pengaruh Kepercayaan, Brand Image dan Kepuasan terhadap Loyalitas Pelanggan Maxim di Kota Batam - Gultom, Christina; Nainggolan, Nora Pitri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid development of digital transportation services has increased competition among service providers, including Maxim in Batam City. However, Maxim faces challenges related to customer trust, brand perception, and inconsistent satisfaction levels, which may hinder long-term customer loyalty. This study aims to examine the influence of trust, brand image, and customer satisfaction on customer loyalty toward Maxim in Batam. A quantitative descriptive method was employed, using a purposive sampling technique to select 204 active Maxim users as respondents. Data were collected through a structured questionnaire and analyzed using multiple linear regression. Prior to hypothesis testing, data validity, reliability, and classical assumptions were assessed to ensure statistical soundness. The findings reveal that trust, brand image, and satisfaction each have a significant positive impact on customer loyalty, with brand image showing the strongest influence (β = 0.447), followed by satisfaction (β = 0.324), and trust (β = 0.243). Together, these three variables explain 71.8% of the variation in customer loyalty. The results suggest that improving brand image, maintaining consistent service quality, and building customer trust are essential strategies for Maxim to retain loyal customers in an increasingly competitive market. This study provides practical insights for digital transportation service providers seeking to strengthen their market position through enhanced customer relationship strategies.